Hukum Internasional:Peran PBB dan Mahkamah Internasional Dalam Konflik Israel dan Palestina - Dicky Firmansyah Dicky (Yayasan Lentera Keadilan Cendikia, 2025)
The conflict between Palestine and Israel is a prolonged and ongoing conflict that continues to clam many lives, especially among civilians and children. This conflict has also been marked by numerous human right violations. These violations include killings, forced evictions, territorial blockades, and attacks on public facilities. Such actions have drawn international attention as they are considered violations of international law. This research aims to analyze the various forms of human rights violations within the conflict from the perspective of international law. Furthermore, this study also explains the role of international institutions, such as the International Court of Justice (ICJ) and the United Nations Human Right Council (UNHRC), in responding the conflict